Critical Educational Gerogogy: Towards Enlightenment and Emancipation - Manuel Solomon; Lorenzo Bowman; Glenn Anthony Palmer (Adult Education Research Conference, 2015)
: This paper examines how critical educational gerogogy (CEG) can be used to expose ageism and relationships of power and inequality in the lives of older adults. The current literature in CEG is reviewed. The authors conclude by advancing a counterhegemonic approach which embraces transformative and emancipative education for older adults.
Keywords: gerogogy; gerontology; older adults; andragogy; adult education